A Theory of Regret - Price, Brian, 1970- (Book collections on Project MUSE., 2017)
Brian Price theorizes regret as an important political emotion that allows us to understand our convictions as habits of perception rather than as the signs of moral courage, teaches us to give up our expectations of what might appear, and prepares us to realize the steps toward changing institutions.